Impact of relaxation therapy on premenstrual symptoms: A systematic review - Ancy Jose; Sabitha Nayak; Aparna Rajesh; Neetha Kamath; M Nalini (Wolters Kluwer Medknow Publications, 2022)
Relaxation therapy (RT) is considered to be helpful in the management of symptoms of premenstrual syndrome (PMS). This systematic review (SR) was conducted to find the impact of RT on PMS management, which could be utilized in clinical and community populations. Five major databases like Google Scholar, PubMed, ResearchGate, Scopus, and Web of Science were used as search engines. The Joanna Briggs Institute checklist is used to analyze the quality of articles selected for this review. Only 35 different studies among 71 relevant articles which focused on the topic were selected for this SR. All of the 35 different trials reported that the selected RTs, namely Laura Mitchell, Jacobson, Benson, relaxation unnamed, yoga, aerobic exercise, and massage, significantly decreased PMS. The outcome of this SR suggests that the selected seven RTs effectively relieve PMS and ensure a productive life for all reproductive women.